Sympathetic Response to Postural Perturbation in Stance - Kawasaki, Taku; Oda, Hitoshi; Sawaguchi, Yasushi; Kunimura, Hiroshi; Hiraoka, Koichi (Frontiers in Human Neuroscience, 2021)
The purpose of the present study was to elucidate whether the sympathetic response to perturbation in stance represents multiple mental responses, whether perturbation-induced fear of fall is one of the mental responses, and whether the sympathetic response is task specific. While healthy humans maintained stance, the support surface of the feet translated in the forward or backward direction. The phasic electrodermal response (EDR), representing the sympathetic response, appeared 1–1.5 s after the support surface translation. Mostly, perturbation-induced EDRs comprised one peak, but some EDRs were comprised of two peaks. The onset latency of the two-peak EDR was much shorter than that of the one-peak EDR. The second peak latency of the two-peak EDR was similar to the peak latency of the one-peak EDR, indicating that the first peak of the two-peak EDR was an additional component preceding the one-peak EDR. This finding supports a view that perturbation-induced EDR in stance sometimes represents multiple mental responses. The amplitude of the EDR had a positive and significant correlation with fear, indicating that perturbation-induced EDR in stance partially represents perturbation-induced fear of fall. The EDR amplitude was dependent on the translation amplitude and direction, indicating that perturbation-induced EDR in stance is a task specific response. The EDR appeared earlier when the participants prepared to answer a question or when the perturbation was self-triggered, indicating that adding cognitive load induces earlier perturbation-induced mental responses.